Mate protection in pre-nesting Canada Geese Branta candensis - Johnson, I P; Sibly, R M (Wildfowl, 1990)
Fourteen individually marked pairs of Canada Geese were observed from january to April on their feeding grounds in the south of England. Mated birds associated closely within the flock. Females spent more time feeding than did their mates, while male geese were more vigilant and more frequently involved in aggressive encounters. Increased aggression by males and females at the centre of the flock could be a consequence of the shorter distances between birds at the middle. Male vigilance was higher at the edge. Male vigilance may protect the mate from potential predators (particularly at the edge of the flock) and possibly from interference by conspecifics. Protection enables females to decrease the time they spent vigilant, and thus increase the time spent feeding, allowing them to gain the reserves of fat and protein needed for successful breeding.